MEASUREMENT OF TRANSMITED VIBRATION TO TRACTOR SEAT - Mudafer Kareem Abdullah; Ahmed Abd Ali Hamid AL-Mafraji (Journal of Engineering, 2011)
A field experiment was conducted at experimental field of Mechanization Agriculture , the College of Agriculture , Abu – Ghraib , University of Baghdad .To measure transmitted vibration to seat tractor during operation tillage , mold board plow with New Holland 66-S- 80 tractor as one machinery unit , Soil was treated at soil constant moisture ( 18 – 20 % ) with two depths of plowing (15 and 20 cm ) and three speed of tractor 2.0 , 3.5, 6.8 km / h . Three main dimensions in seat tractor measurement vertical, longitudinal and lateral acceleration. Split plot design under completes block design with three replicates